Common Brain Substrates Underlying Auditory Speech Priming and Perceived Spatial Separation - Wang, Junxian; Chen, Jing; Yang, Xiaodong; Liu, Lei; Wu, Chao; Lu, Lingxi; Li, Liang; Wu, Yanhong (Frontiers in Neuroscience, 2021)
Under a “cocktail party” environment, listeners can utilize prior knowledge of the content and voice of the target speech (i.e., auditory speech priming, ASP) and perceived spatial separation to improve recognition of the target speech among masking speech. Previous studies suggest that these two unmasking cues are not processed independently. However, it is unclear whether the unmasking effects of these two cues are supported by common neural bases. In the current study, we aimed to first confirm that ASP and perceived spatial separation contribute to the improvement of speech recognition interactively in a multi-talker condition, and further investigate whether there exist intersectant brain substrates underlying both unmasking effects, by introducing these two unmasking cues in a unified paradigm and using functional magnetic resonance imaging. The results showed that neural activations by the unmasking effects of ASP and perceived separation partly overlapped in brain areas: the left pars triangularis (TriIFG) and orbitalis of the inferior frontal gyrus, left inferior parietal lobule, left supramarginal gyrus, and bilateral putamen, all of which are involved in the sensorimotor integration and the speech production. The activations of the left TriIFG were correlated with behavioral improvements caused by ASP and perceived separation. Meanwhile, ASP and perceived separation also enhanced the functional connectivity between the left IFG and brain areas related to the suppression of distractive speech signals: the anterior cingulate cortex and the left middle frontal gyrus, respectively. Therefore, these findings suggest that the motor representation of speech is important for both the unmasking effects of ASP and perceived separation, and highlight the critical role of the left IFG in these unmasking effects in “cocktail party” environments.